The protective role of cognitive reserve in moderating depressive symptomatology in patients with multiple sclerosis - Madia M. Biasi; Paolo Taurisano; Alessia Manni; Vincenzo Mangialardi; Daphne Gasparre; Pietro Iaffaldano; Francesca Caputo; Antonio Iaffaldano; Damiano Paolicelli (BMC Psychology)
Abstract Background The prevalence of cognitive impairment (CI) in Multiple Sclerosis is between 40 and 65% in MS patients, affecting domains like memory, attention, slowed information processing speed, and language. High levels of depression have also been shown to exacerbate cognitive symptoms. However, some studies revealed that greater Cognitive Reserve (CR), protects against cognitive decline in PwMS. This study investigates the role of CR in moderating the effect of depression on cognitive functions in a cohort of 187 Italian PwMS. While acknowledging the influence of anxiety, fatigue, and sleep quality on cognitive performance, our primary focus was on the depression-cognitive function link. Methods 187 PwMS (W = 130; mean age = 42.0 years; SD = 12.5), from the Bari University Hospital, underwent testing for semantic fluency (Word List Generation [WLG]), sustained attention and working memory (Paced Auditory Serial Addition Test [PASAT]), Cognitive Reserve level (Cognitive Reserve Index questionnaire [CRIq]), and depressive symptomatology (Beck’s Depression Inventory [BDI]; ). Results Statistically significant correlations emerged between WLG and CRIq, PASAT and CRIq, WLG and BDI, PASAT and BDI. GLM mediation analyses revealed that the direct effects of depression on PASAT and WLG scores were not statistically significant (p > 0.05). In contrast, the indirect impact (BDI → CR → PASAT and BDI → CR → WLG) was significant (z=-2.29, p < 0.05; z=-2.49; p < 0.05. Conclusion These results suggest that CR moderates the relationship between depressive symptomatology and sustained attention, and between depressive symptomatology and verbal fluency. The evidence indicates that CR benefits MS patients by alleviating cognitive and depressive symptoms, thereby improving their quality of life.